Ancient Auroral Records Compiled From Korean Historical Books. Issue 1 (18th January 2021) - Wang, Yuqi; Chen, Si; Xu, Kaihua; Yan, Limei; Yue, Xinan; He, Fei; Wei, Yong
Abstract: Aurora provides an essential diagnostic to spatial and temporal variations of terrestrial space environment and is also an important proxy of solar and geomagnetic activities. Contemporary auroral observations have just continued for more than half a century. Visual auroral phenomena recorded in historical books provide key clues to understand the solar and geomagnetic activities in the long history prior to modern era. In this study, we compiled a new auroral catalog from ancient Korean historical books, including 2013 auroral records with day‐level resolution from 1012 to 1811 CE, especially for the records searched from the Seungjeongweon Ilgi . The number of auroral records in this new catalog is greatly enlarged compared with previous lists. The occurrence of the aurora in the new catalog is generally consistent with previous data sets. This extended data set provides valuable support for various studies related to solar‐terrestrial space weather and ancient climates in the past millennium. Key Points: A new catalog of historical Korean auroral records during 1012–1811 is compiled The catalog contains 2013 red auroral records with date, local time, and direction information The data set provides valuable support for various studies related to solar‐terrestrial space weather and ancient climates